Digital Effect: Relationship between Brand Media Image and Company Performance - Kuzmin, Evgeny A.; Faminskaya, Marina V.; Rodionova, Elena A.; Zinatullina, Elza R. (SCAD Independent, 2022)
The primary trend of the ongoing digital transformation is the rapid socialization of the Internet. The crucial role in those processes is assigned to social networks. Integrating companies representing goods and services into social networks makes implementing a marketing strategy in a virtual environment urgent. Our literature review looked at the goals of a brand's social media presence and the expected benefits of that presence. Using a correlation-regression analysis, we have established the relationship between the media image of several global companies on social networks and the sales dynamics, value, and awareness of their brand. The hypotheses put forward were partially confirmed. However, the results showed no strong relationship between brand activity and brand audience in a social network and brand value and awareness. On the other hand, there wass a noticeable relationship between the size of the audience in a social network and the dynamics of the brand's revenue. Still, this influence turned out to be the opposite. Thus, the media image of a brand signifies the emergence of a kind of